Efficient radio resource management through coordinated multipoint transmission and carrier aggregation for LTE-advanced / Muhammad Hasibur Rashid Chayon - Muhammad Hasibur, Rashid Chayon (2018)
The demand of high data rate services for mobile user increases sharply nowadays. It is difficult for Long Term Evolution (LTE) to cope up with this current and future requirement. Hence, Long Term Evolution-Advanced (LTE-A) introduces several new technologies to improve the performance of the user. However, poor received signal and interference from adjacent cells in the cell-edge area can reduce the efficiency of using the individual technology. Therefore, the cell-edge users experience lower throughput compared to the LTE-A standard which leads to overall poor system performance. This thesis proposes an efficient downlink radio resource management scheme by implementing Coordinated Multipoint (CoMP) transmission and reception along with Carrier Aggregation (CA) technique to achieve better performance for cell-edge user as well as cell-center user. The proposed method, jointly transmits multiple Component Carriers (CCs) to the cell-edge user from different cells in order to increase the bandwidth, strengthen the received signal and reduce the interference while it satisfies several constraints. The cell-center user gets multiple CCs from the same attached eNodeB (eNB). Modified Largest Weighted Delay First (MLWDF) algorithm is deployed for resource allocation which considers queuing delay, the probability of packet loss, the instantaneous and previous data rate of the user. Extensive system-level simulations for different network scenarios have been performed by a MATLAB based simulator to evaluate the performance of the proposed method. The obtained results show that the proposed method significantly enhances the spectral efficiency, fairness index, cell-edge user throughput and average user throughput compared with the existing conventional methods. The simulation results also illustrate that the proposed method performs better than individual techniques and can be implemented in different network conditions.